2022
DOI: 10.1039/d2cc00247g
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable catalysis with fluxional acridine-based PNP pincer complexes

Abstract: Due to the widespread use of fossil fuels and the resulting global warming, development of sustainable catalytic transformations is now more important than ever to obtain our desired fuels and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 98 publications
0
15
0
Order By: Relevance
“…The fac isomer was calculated to be 9.1 kcal/mol higher in energy than the mer isomer. 67 Interestingly, the DFT studies indicate that two distinct mechanisms are possible for the initial amine dehydrogenation. The first is N–H activation and H 2 liberation, followed by β-hydride elimination, which can proceed without water ( Figure 6 e).…”
Section: Oxidation Of Amines By Watermentioning
confidence: 99%
See 2 more Smart Citations
“…The fac isomer was calculated to be 9.1 kcal/mol higher in energy than the mer isomer. 67 Interestingly, the DFT studies indicate that two distinct mechanisms are possible for the initial amine dehydrogenation. The first is N–H activation and H 2 liberation, followed by β-hydride elimination, which can proceed without water ( Figure 6 e).…”
Section: Oxidation Of Amines By Watermentioning
confidence: 99%
“…The reaction requires a catalytic amount of base to convert the employed precatalyst 5c to the actual catalyst. Mechanistic investigations revealed that in the presence of base and cyclic amine, the aromatic complex 5c is first converted to a dearomatized complex 6 , which then catalyzes the reaction (Figure c). , Consequently, the dearomatized complex 6 catalyzes the reaction even under neutral conditions in the absence of base. Important insights regarding the catalytic cycle were obtained by DFT studies.…”
Section: Oxidation Of Amines By Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Its distinct photophysical properties such as strong emission and long lifetime in the excited states are utilized not only for biological and material sciences but also for organic photocatalysis such as acridinium salts . While acridine-based PNP-pincer ligands and complexes have recently been developed for some catalytic reactions, transition metal–acridine complexes have not been applied to photochemical reactions . We suppose that visible-light excitation of the metal–acridine complex would induce metal-to-ligand charge transfer (MLCT) efficiently, generating a highly reactive electron-deficient metal center.…”
Section: Introductionmentioning
confidence: 99%
“…1), which have previously shown good catalytic activities for the transformation of different carbonyl and alcohol functionalities. 21,22,[26][27][28][29][30][31][32][33][34][35][36][37][38] We also studied the addition of a cosolvent to maximize the productivity of the catalyst under ADC conditions for the transformation of EtOH.…”
mentioning
confidence: 99%